A Survey of UK Centres on Low Iodine Diet Recommendations prior to Radioiodine Ablation Therapy for Differentiated Thyroid Cancer. Issue 3 (17th May 2020) - England, Clare Yvonne; Moss, Laura; Beasley, Matthew; Haupt-Schott, Ingrid; Herbert, Georgia; Atkinson, Charlotte
Abstract : Background: Guidelines suggest that a low iodine diet (LID) is advised prior to radioiodine ablation (RIA) for thyroid cancer. We aim to describe current practice regarding LID advice in the UK, determine uptake of the 2016 UK LID Working Group diet sheet and discover whether there are differences in practice. Methods: We used an online survey distributed between November 2018 and April 2019 to centres in the UK that administer 131 I. We asked questions on whether a LID is advised, for how long, how advice is presented, whether and how compliance is measured and whether treatment is delayed if LID advice is not followed. Results: Fifty-six clinicians from 47 centres that carry out RIA for thyroid cancer responded. Forty-four centres (94%) advise a LID prior to RIA, the majority for 14 days (82%). Two-thirds of the centres use the UK LID Working Group diet sheet. Patients are told to resume normal eating when 131 I is administered at 17 centres (39%), with 18 (41%) advising waiting for 24–48 h after administration. Most centres (95%) use only a simple question or do not assess compliance. Only 2 (5%) indicate that RIA would be delayed if someone said they had not followed LID advice. Conclusions: UK practice regarding LID prior to RIA for thyroid cancer is consistent with current guidelines, but non-adherence does not usually delay RIA. The UK Low Iodine Diet Working Group diet sheet is widely recognised and used. Practice could be improved by centres working to harmonise advice on when to restart a normal diet.